The Prefab People - Tarr, Béla; Mihók, Barna; Pap, Ferenc; Pogány, Judit; Koltai, Róbert; Ambrus, Kyri (Facets Video, 2005)
The last of Béla Tarr's trio of domestic dramas, "The Prefab People" follows the day-to-day struggle of a young couple trying to make a better life. The husband seeks escape from his monotonous job, while the wife needs more help from her husband to raise the family. Along with "Family Nest" and "The Outsider", this film explores the struggles of everyday life in a gripping documentary style. Celebrated for his nihilistic tales of desperate people unable to escape their human or social conditions, Tarr is one of the most distinctive talents in world cinema. He first drew international acclaim with his domestic trilogy. Hauntingly real, the films have been compared to the work of John Cassavetes and hailed as the work of a master director. [Cover]
Keywords: DVD-Video